THE USING OF GRAMMAR CHECKER APPLICATION AND STUDENT’S ABILITY IN ACADEMIC WRITING - Ramadhani, Putri; Darmin, Darni binti (VISION, 2024)
Writing is an activity to mark or convey ideas or to interprete utterance in language into a visible symbol. In university level, writing skill is highly needed by the students to convey their idea. Students are demanded to write academic writing to succeed them to write paper, report, essay and thesis effectively. In indonesia, most of universities demand their undergradutae  students to write thesis as the requirement to pursue the degree. The practice of academic writing in university level not only discuss about how to write descriptive, analytical, persuassive and critical writing, but the most detail in those four main types of academic writing is about how to write correctlty of  the punctuation, spelling and grammar. The need of correct details in academic writng like punctutation, spelling and grammar usually needed by EFL (English as Foreign Language) students. Nowadays, students are well-assisted by the application which help the students to correct their grammar automatically when they type by using computer. Grammar checker is one of the most used application automatically correct students’ grammar in their computer. The investigation aimed to find out how effective the use of grammar checker application to help EFL students in completing their task of academic writing in English. To find the answer, the reasearchers observed and interviewed the students after they completed some observation phases. The result show that grammar checker improved the quality of their writing.